The Influence of User Interactivity, Visual Appeal, and Mental Imagery in Virtual Tourism on Tourist Visit Intentions (A Study of Indonesian Cultural Tourism) - Paulina, Retno; Abas, Novel Idris (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to analyze the influence of User Interactivity, Visual Appeal, and Mental Imagery in virtual tourism on Tourists' Visit Intention toward Indonesian cultural destinations, with a particular focus on the Borobudur Temple virtual tour. The research applies the Stimulus–Organism–Response (S-O-R) framework to explain how interactive digital experiences and visual aesthetics shape tourists' emotional and cognitive responses, which in turn affect their visit intentions.This quantitative study involved 415 respondents who have experienced or accessed virtual tourism platforms showcasing Indonesian cultural sites. Data were collected using an online questionnaire and analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM) through SmartPLS software. The results show that User Interactivity and Visual Appeal have a significant positive effect on Mental Imagery, while Mental Imagery significantly mediates the relationship between those variables and Tourists' Visit Intention. Furthermore, the study finds that the more engaging and visually appealing the virtual tourism experience, the stronger the mental imagery and intention to visit the real destination.The findings emphasize the importance of enhancing interactive and visual elements in virtual tourism as an effective digital marketing strategy for promoting Indonesia's cultural heritage. This research contributes both theoretically and practically to the development of digital-based tourism promotion models, supporting sustainable cultural tourism through immersive virtual experiences.